Penjaminan Mutu pada Learning Outcomes Pondok Pesantren - Khoirun Nisa' (Menara Tebuireng, 2019)
The seminary is the oldest Islamic institution in Indonesia. So in this case there needs to be development and renewal, in order that the boarding school was not outdated. In an effort to improve the quality and characteristics of comprehensive description is from the field or service that shows in the ability to satisfy the needs of the expected or implied. In the context of education, the notion of quality includes input, process, and output of education. The motion of national development or challenge nowadays has been on a "modern" era. The era was marked by advances in science and technology as well as in its utilization. This triggered the birth of the implementation of strategic management in quality improvement efforts on education in boarding schools are increasingly demanding for expertise and specificities in the handle it, and puts this era as the era of human resources. To that end, enhance the quality of the institution required human resources that have skills that are relevant to the needs of education planning. Agency boarding schools are bound by the values and norms of the institutional mission. These values are derived from the values that are in the education institutions boarding schools to increase professionalism in the improved quality of education